Perkembangan dan Pola Pembinaan Pendidikan Anak Usia Dini - Nur Saffanah (Atthiflah: Journal of Early Childhood Islamic Education, 2019)
In this millennium era the level of community needs for an education, especially early childhood education is increasing. As a result, since early 2000 several PAUD began to appear and increasingly buried in the district of Gresik. This increase in quantity should also be followed by strengthening the quality and academic value provided by these institutions, so as to provide appropriate educational services to the surrounding community. Based on this thought, this study tries to describe objectively how the improvement and development of PAUD in several regions of Gresik district, the pattern of guidance carried out by the relevant agencies in order to maintain the quality and academic quality provided, then at the end of the study conclusions of the factors that support the development of PAUD provided by related institutions, and also at the same time underlines several factors that can be a stumbling block for the development of PAUD in the Gresik district.